EXAMINING THE IMPACT OF MATHEMATIC GAMIFICATION ON PRIMARY SCHOOL STUDENT’S ATTITUDE TO MATHEMATICS HOMEWORK - Njoku, MacJoseph C. (Journal of Advance Research in Mathematics and Statistics (ISSN 2208-2409), 2022)
Technology has increasingly been integrated into the educational systems of developing nations, including Nigeria. The trend has contributed immensely to the development of many learning institutions and individual capacity building. The primary school system represents the beginning of learning and reflects a prime period to develop learning attitudes. Teachers use homework to augment classroom learning and improve performance. However, indications suggest that primary school students avoid mathematics homework. The present study examined the effect of a math game app (Prodigy) on students' math homework behavior. A quasi-experimental design was adopted, and the samples were grouped into experimental groups (N=58), exposed to the prodigy app, and control group (N=55), taught in conventional circumstances. The experiment consisted of 24 sessions stressed over three months. Participants were engaged in two sessions per week, lasting about 50 minutes. The findings indicated a mean difference (MD = 12.71) between the post-test study groups. Also, the result revealed a significant difference between the experimental and control group on homework behavior t (111) = 6.132, p = .001. The result has implications for mathematics development.